2018
DOI: 10.1007/s12035-018-1075-z
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Zn2+ Influx into Nigral Dopaminergic Neurons Plays a Key Role for Pathogenesis of 6-Hydroxydopamine-Induced Parkinson’s Disease in Rats

Abstract: Parkinson's disease (PD) is a progressive neurological disease characterized by a selective loss of nigrostriatal dopaminergic neurons. The exact cause of the neuronal loss remains unclear. Here, we report a unique mechanism of nigrostriatal dopaminergic neurodegeneration, in which extracellular Zn influx plays a key role for PD pathogenesis induced with 6-hydroxydopamine (6-OHDA) in rats. 6-OHDA rapidly increased intracellular Zn only in the substantia nigra pars compacta (SNpc) of brain slices and this incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Zinc exposure has been identified as an environmental risk factor for PD [31] and post-mortem studies revealed excessive zinc depositions in the substantia nigra (SN) and the striatum of patients with idiopathic PD [13,[32][33][34][35]. In line with these observations, in vitro and in vivo experiments with animal models of PD showed that cytosolic accumulation labile zinc is a hallmark of degenerating dopaminergic neurons [36][37][38][39][40][41][42]. Importantly, treatments with intracellular zinc chelators prevent neurodegeneration caused by many neurotoxins (6-OHDA, MPTP, and paraquat) confirming that cytosolic Zn 2+ accumulation contributes to dopaminergic neuronal loss [43][44][45].…”
Section: Zinc Excess and Parkinson's Diseasementioning
confidence: 85%
See 1 more Smart Citation
“…Zinc exposure has been identified as an environmental risk factor for PD [31] and post-mortem studies revealed excessive zinc depositions in the substantia nigra (SN) and the striatum of patients with idiopathic PD [13,[32][33][34][35]. In line with these observations, in vitro and in vivo experiments with animal models of PD showed that cytosolic accumulation labile zinc is a hallmark of degenerating dopaminergic neurons [36][37][38][39][40][41][42]. Importantly, treatments with intracellular zinc chelators prevent neurodegeneration caused by many neurotoxins (6-OHDA, MPTP, and paraquat) confirming that cytosolic Zn 2+ accumulation contributes to dopaminergic neuronal loss [43][44][45].…”
Section: Zinc Excess and Parkinson's Diseasementioning
confidence: 85%
“…More recently, Tamano and colleagues showed that increased cytosolic levels of toxic Zn 2+ can also be caused by the influx of extracellular zinc into dopaminergic neurons [ 39 , 40 , 41 ]. In brain slices, both 6-OHDA and paraquat have been found to rapidly increase intracellular Zn 2+ levels only in the SNc.…”
Section: Zinc Dyshomeostasis and Parkinson’s Diseasementioning
confidence: 99%
“…10 -8 to 10 -12 M), and cytosolic MTs exist mostly in the form of Zn 5 MT under physiological (static) conditions, which has the capacity to capture two more free Zn 2+ . 70,71) Thus, it is estimated that hippocampal MTs can buffer 130 nM of free Zn 2+ in the cytosol of young rats. Even if the cytosolic Zn 2+ concentration reaches the extracellular concentration (approx.…”
Section: Perspective On a Defense Strategy Against Neurodegeneration mentioning
confidence: 99%
“…When the increase in intracellular Zn 2+ -buffering capacity is compared between the young and aged hippocampus, as determined based on the reduction in intracellular ZnAF-2 fluorescence, after the systemic administration of dexamethasone, there is no appreciable different between them. 47) Therefore, a blood-brain barrier-permeable MT-inducing agent may be promising for preventing neurodegenerative disorders such as AD linked with intracellular Zn 2+ toxicity 72) (Fig. 2).…”
Section: Perspective On a Defense Strategy Against Neurodegeneration mentioning
confidence: 99%
“…Parkinson's disease (PD) is a progressive neurodegenerative disease associated with aging, which is characterized by the selective loss of nigrostriatal dopaminergic neurons (1)(2)(3). PD is the second most common neurodegenerative disease in the world with a prevalence that is estimated to reach between 8.7 and 9.3 million by 2030 (4).…”
Section: Introductionmentioning
confidence: 99%